Methane and Hydrogen Sulfide Production from the Anaerobic Digestion of Fish Sludge from Recirculating Aquaculture Systems: Effect of Varying Initial Solid Concentrations - Abhinav Choudhury; Christine Lepine; Christopher Good (Fermentation, 2023)
Recirculating aquaculture systems (RAS) are efficient at solid waste capture and collection but generate a concentrated waste stream. Anaerobic digestion (AD) could be one potential treatment option for RAS facilities. However, the concentration of organic matter in the sludge can significantly affect the biogas quality from AD. This study evaluated the effect of fish sludge (FS) solid concentration on biogas quality. Three FS treatments consisted of different initial total solid concentrations (1.5%, 2.5%, and 3.5%) from a mixture of sludge produced by Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss). Methane (CH4) production was measured, quantified, and normalized on a volatile solids (VS) basis. The highest solid concentration treatment produced 23% more CH4 than the lowest solid concentration (519 mL/g VS versus 422 mL/g VS, respectively). Peak CH4 production occurred on Day 7 for the lowest FS concentration (78.2 mL/day), while the highest FS concentration peaked on Day 11 (96 mL/day). Peak hydrogen sulfide (H2S) concentrations ranged from 1803–2074 ppm across treatments, signifying the requirement of downstream unit processes for H2S removal from biogas. Overall, this study demonstrated that increasing the FS concentration can significantly enhance CH4 production without affecting the stability of the digestion process.